Enhanced Publications: Data Models and Information Systems - Bardi, Alessia; Manghi, Paolo (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2014)
“Enhanced publications” are commonly intended as digital publications that consist of a mandatory narrative part (the description of the research conducted) plus related “parts”, such as datasets, other publications, images, tables, workflows, devices. The state-of-the-art on information systems for enhanced publications has today reached the point where some kind of common understanding is required, in order to provide the methodology and language for scientists to compare, analyse, or simply discuss the multitude of solutions in the field. In this paper, we thoroughly examined the literature with a two-fold aim: firstly, introducing the terminology required to describe and compare structural and semantic features of existing enhanced publication data models; secondly, proposing a classification of enhanced publication information systems based on their main functional goals.